Relative contribution of breed, gender, and diet to the fatty acid profile of young crossbred beef cattle finished on feedlot - Silva, M. L.P. [UNESP]; Juárez, M.; Nassu, R. T.; Tullio, R. R.; Berndt, A.; Alencar, M. M.; Rolland, D. C.; Dugan, M. E.R. (Canadian Science Publishing, 2017)
Fatty acid profile of crossbred beef cattle fed either a diet with corn gluten and protected fat (A) or a control diet (B) was evaluated. Animal’s gender and diet had greater influence on fatty acid profile than genotype. Diet A increased polyunsaturated fatty acids/saturated fatty acids ratio and decreased t11/t10-18:1 ratio and n-6 content.
Keywords: Bulls; Energy diet; Heifers; N-3; N-6; PUFA/SFA ratio